2021
DOI: 10.1111/sms.14062
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in elite‐level women’s football—a two‐year prospective study in the Irish Women’s National League

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 36 publications
5
32
0
Order By: Relevance
“…In this context, a systematic review and meta-analysis conducted by (52), reported an overall injury incidence in soccer football players being 6.1 injuries /1000 h exposure, out of which a number of match injury incidence (19.2 injuries / 1000 h of exposure) about 6 times higher than training injury incidence rate (3.5 injuries / 1000 h of exposure). However, Horan D and colleagues were in the same line with their ndings from the Irish Women's National League (54), reporting a 7.9 injuries / 1000 h exposure overall injury incidence ratio with an even higher difference (7.5 times) in between match (192 / 1000 h) and training (2.5 / 1000 h). Another recent study from the rst division of Spanish Women's Soccer League (53), reported an injury incidence ration of 3.65 injuries / 1000 h with an even higher match versus training injury incidence ratio (19.02 / 1000 h and 1.70 / 1000 h, respectively).…”
Section: Incidence Rate Of Overall Injurymentioning
confidence: 56%
See 1 more Smart Citation
“…In this context, a systematic review and meta-analysis conducted by (52), reported an overall injury incidence in soccer football players being 6.1 injuries /1000 h exposure, out of which a number of match injury incidence (19.2 injuries / 1000 h of exposure) about 6 times higher than training injury incidence rate (3.5 injuries / 1000 h of exposure). However, Horan D and colleagues were in the same line with their ndings from the Irish Women's National League (54), reporting a 7.9 injuries / 1000 h exposure overall injury incidence ratio with an even higher difference (7.5 times) in between match (192 / 1000 h) and training (2.5 / 1000 h). Another recent study from the rst division of Spanish Women's Soccer League (53), reported an injury incidence ration of 3.65 injuries / 1000 h with an even higher match versus training injury incidence ratio (19.02 / 1000 h and 1.70 / 1000 h, respectively).…”
Section: Incidence Rate Of Overall Injurymentioning
confidence: 56%
“…Many studies have been investigating soccer-related injuries played in various major soccer leagues (27,28,(52)(53)(54), many of which show signi cant differences across countries in the frequency of injuries. In this study, the elite women's soccer league's overall injury rate was observed in Kosovo is 3.21 (CI: 1.24, 3.27), which was surprisingly lower than in other studies.…”
Section: Incidence Rate Of Overall Injurymentioning
confidence: 99%
“…The categorization of the type of injury followed the UEFA model [ 10 ]. To designate the part of the body where the injury was produced, a classification endorsed by other authors was used [ 34 ]. Four demarcations were used for the analysis [ 1 ] and divided the match into 15 min intervals [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we do not recommend using this term, nor do we recommend using the term subelite for the same reason. The term elite is often used, especially in women’s football, even if they are amateurs,33 but it is rarely defined sufficiently. Unfortunately, league systems and the corresponding definitions of elite, vary from association to association (country to country) and from confederation to confederation 34.…”
Section: Consensus Recommendationsmentioning
confidence: 99%